THE ANALYSIS OF MARKETING STRATEGY FOR INDOMIE IN SOUTH KOREA - Jovita, Karina
Indomie is a popular instant noodle brand that originated in Indonesia and has gained significant market share in various international markets. South Korea is a highly competitive market for instant noodles, with numerous local and international brands vying for consumer attention. Indomie aims to increase its market share in South Korea by analyzing its current marketing strategy and adapting it to meet the preferences of South Korean consumers. To do the analysis, it is needed to do environmental scanning which consists of external and internal environment analysis. To analyze the external environment, this research used General Environment Analysis theory and industry analysis using Porter Five Forces. The external environment also includes customer analysis using STP, Marketing Mix, and competitor analysis using comparison methods. Meanwhile, for the internal analysis, this research is using VRIO Analysis. Furthermore, the strategy can be formulated using Strategic Diamond Model and Proposed Marketing Mix. The research will examine the factors that have led to the success of Indomie in other international markets and how these factors can be adapted to the South Korean market. The study will use both primary and secondary data sources to analyze consumer preferences, market trends, and competition. Based on the analysis, the study will provide recommendations on how Indomie can improve its marketing strategy to increase its market share in South Korea. The findings of this study will be relevant not only to Indomie but also to other international companies seeking to enter the South Korean market. From the results of all analyzes, Indomie is advised to implement some of new strategies. It is because, based on external analysis, the instant noodle industry in South Korea is considered as unfavorable – the number of competitors that keep increasing, and a lot of substitute products. However, it does not prevent people from opening a business in this field. It is proven by the increasing the number of competitors in the market. Therefore, Indomie need to differentiate its product from other instant noodle brands in South Korea by emphasizing unique product features. Indomie can also adapt its product to meet the preferences of South Korean consumers. Moreover, Indomie could form partnerships with another local distributors or retailers that have a same vision to aggressively penetrate the market where this could involve collaborating with popular food bloggers or influencers too. Promotion also plays an important role on how to increase the sales performance of Indomie in South Korea with the objective to keep prices low to compete with other brands in the market.